Tata Kelola Kolaborasi Pengembangan Kampung Wisata Berbasis Masyarakat - Deden Saputra (Departemen Ilmu Pemerintahan Fisip Unhas, 2020)
Tamansari tourism village is one of the tourist villages in the City of Yogyakarata which is included in the Stubs category. Of course this is not expected, because Tamansari tourism village has a lot of potential. Community-based tourism development collaboration is the answer to overcome these problems. The concept of collaboration in the development of community-based tourism is expected to make Tamansari tourism village develop or be independent. This research method uses descriptive qualitative type, in knowing tourism collaboration management, data analysis is used by emphasizing structured and unstructured interview instruments in order to obtain complete data. This research concludes that the collaboration does not fully implement the principles of collaboration, and the collaborative process does not work in synergy. The results showed that stakeholders who played a direct role in tourism development were the Yogyakarta city tourism office, Patehan village head, academics, village tourism managers, and tourism service providers / providers. The pattern of cooperation between the government and the community is in the form of guidance, and collaboration between the academics and the community is in the form of studies. Exclusive facilitative and institutional leadership has become an obstacle to the collaborative process of developing Tamansari tourism village.